BELAJAR DARI KECERDASAN LOKAL: STUDI TENTANG KAMPUNG NAGA - Pancawati Dewi (ATRIUM: Jurnal Arsitektur, 2018)
Title: Learning from the Local Intelligence: Study in Kampung Naga Changes that occur in Kampung Naga houses can not be avoided. Change is adapted to the development of the times adjusting to the evolving socio-economic and cultural conditions. The method used in this study is the Interpretive-Historical. The key to this research method is interpretation. This is done to try to understand the phenomena that exist in the field (a subjective group of people) and bring them to an objective interpretation. Material changes to the layout and the house can not be avoided in order to customize their new needs and technology of today. Changing patterns of house structure and the addition of new space shows the friendliness and openness of Kampung Naga society in welcoming the tourists. The effort to preserve their traditions still shows strong identity in Kampung Naga society in the face of changing times. Placement the hearth at this time is tend to be permanent, though it can be shifted layout. The hearth has an important role in people's daily lives in Kampung Naga since old time to be maintained to this day.